The Importance of Digital Literacy for Society 5.0 : A Phenomenological Approach - Sandra, Jana; Yuliawan, Yuliawan (Technium Social Sciences Journal, 2022)
Every individual needs to understand that digital literacy is an important thing needed to be able to participate in today's modern world. Digital literacy is as important as reading, writing, arithmetic, and other disciplines. Everyone should be responsible for how to use technology to interact with the surrounding environment. This research is intended to answer the question of how Indonesian people understand the importance of digital literacy and what kinds of efforts must be taken to improve the digital literacy of the Indonesian people. Data collection was carried out by unstructured interviews with 21 informants consisting of secondary school students, college students, employees, housewives, and IT expert. The results of this study prove that from the 4 pillars of digital literacy, namely digital skills, digital culture, digital ethics and digital safety, there are two factors that really need to be improved by Indonesian people today, namely digital ethics and digital safety. Some efforts are needed to be implemented by involving relevant stakeholders in education, community organisations, government institutions as well as private sectors, not only in the form of socialisation but also other educational activities such as seminars and FGDs.